Five new species of Geranomyia Haliday, 1833 (Diptera, Limoniidae) from China - Zhang, Xiao; Zhang, Zehua; Yang, Ding (Zootaxa, 2016)
The following five new species of the genus Geranomyia from China are described and illustrated: G. baisensis sp. nov., G. degenerata sp. nov., G. longispina sp. nov., G. maculata sp. nov. and G. nigra sp. nov.. Three known species, G. apicifasciata (Alexander, 1930), G. radialis (Alexander, 1930) and G. sparsiguttata (Alexander, 1937), are listed with new distribution data. A key to the species of the genus Geranomyia from China is presented.